1991
DOI: 10.1136/gut.32.3.260
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of fluticasone propionate in untreated coeliac disease.

Abstract: Although gluten withdrawal is likely to remain the mainstay of treatment for adult coeliac disease, many patients find the diet inconvenient and unpalatable and compliance among asymptomatic patients is often poor. Oral corticosteroids have been used for patients who seem to be resistant to gluten withdrawal but preparations with low systemic bioavailability might be preferable. We have given a new glucocorticoid (fluticasone propionate) to 12 adults with untreated coeliac disease for six weeks while they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…This success was later translated into a clinical study: Bramble et al [9] reported symptomatic improvement in patients taking locally active corticosteroids despite their continuation of a regular diet. These results were later confirmed by Mitchison et al [10], who reported clinical and histological improvement in celiac patients consuming a regular diet while taking a locally active corticosteroid. The success of these studies was somewhat mitigated by the finding that systemic corticosteroid absorption occurred.…”
supporting
confidence: 60%
“…This success was later translated into a clinical study: Bramble et al [9] reported symptomatic improvement in patients taking locally active corticosteroids despite their continuation of a regular diet. These results were later confirmed by Mitchison et al [10], who reported clinical and histological improvement in celiac patients consuming a regular diet while taking a locally active corticosteroid. The success of these studies was somewhat mitigated by the finding that systemic corticosteroid absorption occurred.…”
supporting
confidence: 60%
“…It might be expected that immunosuppressive treatment moderates this overactivity and thus might be a valuable treatment option. The use of several immunosuppressive treatment strategies such as corticosteroids, cyclosporin and interleukin‐10 (IL‐10) has been described in RCD patients and untreated coeliac disease patients, mainly in case reports, but with disappointing results in the majority of cases 14–22 . Of course, the positive effects of corticosteroids 16 , 20 are counteracted by their disadvantages, such as fluid retention and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Bramble et al 29 . and Mitchison et al 30 . used topically active corticosteroids in patients with coeliac disease that were on a regular diet and noted improvements in both histology and parameters of absorption.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Second, this class of drug has been demonstrated to be efficacious in coeliac disease. Bramble et al 29 and Mitchison et al 30 used topically active corticosteroids in patients with coeliac disease that were on a regular diet and noted improvements in both histology and parameters of absorption. Budesonide is currently used in the treatment of refractory coeliac disease and in enteropathy associated T cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%